2006
DOI: 10.1016/j.fluid.2006.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Application of extended scaling law to the surface tension of fluids of wide range of molecular shapes

Abstract: A linear correlation is presented between the reduced surface tension * σ and reduced temperature * extScal S acts as an intermediate equation to derive a new analytical expression for s µ E in terms of intensive physical and thermodynamic properties of the particular fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The overall AAD of the predicted surface tension for 81 data points using the present model, Alavianmehr et al, QSPR, and CS-GC methods were found to be 0.29, 1.45, Table 7 The scaling constants to be used in Eq. (25)and AAD (%) of the calculated surface tension using the present model and those obtained by Alavianmehr et 7.73, and 4.14%, respectively. As we can see from Table 7, the present model is the most accurate among other abovementioned methods.…”
Section: Extension To Mixturessupporting
confidence: 62%
See 1 more Smart Citation
“…The overall AAD of the predicted surface tension for 81 data points using the present model, Alavianmehr et al, QSPR, and CS-GC methods were found to be 0.29, 1.45, Table 7 The scaling constants to be used in Eq. (25)and AAD (%) of the calculated surface tension using the present model and those obtained by Alavianmehr et 7.73, and 4.14%, respectively. As we can see from Table 7, the present model is the most accurate among other abovementioned methods.…”
Section: Extension To Mixturessupporting
confidence: 62%
“…Surface tension of a liquid is related to the intermolecular interaction potential energy and the liquid interfacial microstructure; it decreases linearly with temperature in the range of freezing to the boiling temperature and vanishes non-linearly close to the critical point [23][24][25][26]. Like viscosity, surface tension can be measured with high accuracy.…”
Section: Introductionmentioning
confidence: 99%